เว็บไซต์มหาวิทยาลัยเที่ยงคืนในฐานะสื่อประชาสังคม - เจษฎา เจนพิทักษ์ชาติ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research has been conducted qualitatively with the purpose of studying the role of the Midnight University website (www.midnightuniv.org) as a form of civil journalism that utilizes the unique qualities of the internet media to empower users, and the webmaster’s role as the information gatekeeper in the 2.0 era of this website. This research also studies the users of the Midnight University website, the various ways that they benefit from the information gained from the website, and the problems and obstacles they face in attaining information from the website. Data was collected through in-depth interviews and analysis of web board contents. Research results acquired through the interviews of a sample group of nine and the analysis of web board contents during two time periods demonstrates that the Midnight University website is very useful due to its presentation of academic articles that include new socio-political context, which are difficult to find elsewhere. The knowledge provided in the website could be adopted in other forms of studies and academic work. However, this website fails to serve effectively as the medium for civil journalism due to the highly academic language used to present its contents, which is an important obstacle to the comprehension of the average users. Consequently, regular users of the Midnight University website are limited to academics, professors, students, and users who are truly interested in the topics presented. Moreover, users must possess basic knowledge about computers and the internet. This prevents successful communication with a wider audience. The use of public space is another important factor. This website has been closed down many times due to accusations of lèse-majesté which stemmed from opinions expressed by certain users on the Midnight University web board. Therefore, the webmaster has solved the problem by allowing users to express their opinions only by posing a new discussion thread. This method makes it easier for the webmaster to check and censor seditious comments. However, this problem-solving method has cause discontent among certain groups of users who view that this is a way of imposing the webmaster’s burden upon the users as well as causing discontinuity in the exchange of ideas and opinions. Thus, the web board’s popularity has decreased significantly, forcing the webmaster to post more information in order to encourage activity within the web board. Moreover, the form of internet communication has changed from what it used to be in the past. That is, according to web 2.0 analysis, users are becoming more and more like content providers. The webmaster’s traditional role as the information gatekeeper—allowing only selected information to be published both as articles and opinion statements on the web board—has caused users to doubt the webmaster’s personal discretion. This is because they believe that the webmaster’s job is only to provide a public space for discussion and accord the highest level of convenience to the users. These problems have resulted in users entering the website only to read articles. Consequently, there is no sense of community in the web board. Opinions expressed tend to go unchallenged. Hence, it is doubtful whether or not this website would be able to encourage the driving force for any social change. Furthermore, the research suggests that users would like the website to be developed in many practical aspects—for example, decorating images, fonts, background colors, utility features—so that it would become more user-friendly and more convenient. The Midnight University website should also expand its channels of communication so as to allow participation from a greater community of users.